Comparison of Effects of Using Geosynthetics and Lime Stabilization to Increase Bearing Capacity of Unpaved Road Subgrade - Erhan Burak Pancar; Muhammet Vefa Akpınar (Advances in Materials Science and Engineering)
So many soil improvement methods have been developed in order to increase bearing capacity of superstructure of the road to be constructed on the soft clayey road base soils, decrease settlements, and increase other strength specifications (CBR, k, MR values, etc.). In this paper, lime stabilization of clayey road base soil with high water content and its improvement with geosynthetics (geocell + geotextile) reinforcement and comparisons of these two different improvement methods were made. For this purpose, plate loading experimental comparisons of clayey soil, which had high water content by 10% increasing the optimum water content, were made after it was improved with lime at the rates of 3, 6, and 12%, geotextile reinforcement, geocell reinforcement, geosynthetics reinforcement, and geosynthetics reinforcement + lime stabilization at various rates. It was understood that these improvement methods will not yield sufficient results on clayey soils with high water content on their own, and method of improvement with lime and then reinforcement with geosynthetics yields better results on these types of soils. Only one improvement state among ten different states examined in this study gave the sufficient results for the soil to be used for unpaved roads.